The heart in Duchenne muscular dystrophy: early detection of contractile performance alteration - Wagner, Sören; Weber, Cornelia; Hein, Selina; Schinkel, Stefanie; Walther, Andreas; Bekeredjian, Raffi; Müller, Oliver J.; Friedrich, Oliver (Journal of cellular and molecular medicine, 2012)
Progressive cardiomyopathy is a major cause of death in Duchenne muscular dystrophy (DMD) patients. Coupling between Ca2+ handling and contractile properties in dystrophic hearts is poorly understood. It is also not clear whether developing cardiac failure is dominated by alterations in Ca2+ pathways or more related to the contractile apparatus. We simultaneously recorded force and Ca2+ transients in field-stimulated papillary muscles from young (10-14 weeks) wild-type (wt) and dystrophic mdx mice. Force amplitudes were fivefold reduced in mdx muscles despite only 30 % reduction in fura-2 ratio amplitudes. This indicated mechanisms other than systolic Ca2+ to additionally account for force decrements in mdx muscles. pCa-force relations revealed decreased mdx myofibrillar Ca2+ sensitivity. ‘In vitro’ motility assays, studied in mdx hearts here for the first time, showed significantly slower sliding velocities. mdx MLC/MHC isoforms were not grossly altered. Dystrophic hearts showed echocardiography signs of early ventricular wall hypertrophy with a significantly enlarged end-diastolic diameter ‘in vivo’. However, fractional shortening was still comparable to wt mice. Changes in the contractile apparatus satisfactorily explained force drop in mdx hearts. We give first evidence of early hypertrophy in mdx mice and possible mechanisms for already functional impairment of cardiac muscle in DMD.